2018
DOI: 10.1074/jbc.ra117.001073
|View full text |Cite
|
Sign up to set email alerts
|

The cellular stress proteins CHCHD10 and MNRR1 (CHCHD2): Partners in mitochondrial and nuclear function and dysfunction

Abstract: Coiled-coil-helix-coiled-coil-helix domaincontaining 10 (CHCHD10) and CHCHD2 (MNRR1) are homologous proteins with 58% sequence identity and belong to the twin CX 9 C family of proteins that mediate cellular stress responses. Despite the identification of several neurodegeneration-associated mutations in the CHCHD10 gene, few studies have assessed its physiological role. Here, we investigated CHCHD10's function as a regulator of oxidative phosphorylation in the mitochondria and the nucleus. We show that CHCHD10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
2
48
0
Order By: Relevance
“…Like mitofilin and L‐OPA1, we observed no detectable differences in the overall levels of Mfn2, Drp1, or CHCHD2 proteins. However, we cannot rule out the possibility that different complexes of these proteins are altered by CHCHD10 mutations, particularly CHCHD2, which has been reported to form a complex with CHCHD10 44,50‐52 . Interestingly, a recent study using a Drosophila model reported that the WT version of Drosophila CHCHD2 increases OPA1 levels, while CHCHD2 mutations decrease OPA1 through as yet unknown mechanism 53 …”
Section: Discussionmentioning
confidence: 93%
“…Like mitofilin and L‐OPA1, we observed no detectable differences in the overall levels of Mfn2, Drp1, or CHCHD2 proteins. However, we cannot rule out the possibility that different complexes of these proteins are altered by CHCHD10 mutations, particularly CHCHD2, which has been reported to form a complex with CHCHD10 44,50‐52 . Interestingly, a recent study using a Drosophila model reported that the WT version of Drosophila CHCHD2 increases OPA1 levels, while CHCHD2 mutations decrease OPA1 through as yet unknown mechanism 53 …”
Section: Discussionmentioning
confidence: 93%
“…1,6 CHCHD10 forms part of the multiprotein complex MICOS, which plays a vital role in the formation and maintenance of cristae structure. 7 A recent study 8 demonstrated that CHCHD10 is a regulator of mitochondrial respiration and can contribute to transcriptional repression of oxygen-responsive element containing genes, and some genetic CHCHD10 variants (G66V and P80L) are impaired in these activities.…”
Section: Discussionmentioning
confidence: 99%
“…CHCHD10 is strongly expressed in muscle and heart and in specific cell types of the central nervous system (CNS), including dopaminergic neurons of the midbrain and motor neurons in the spinal cord [1,4,15]. Although the normal roles of CHCHD10 and CHCHD2 remain unknown, both proteins have short half-lives [4,30,35], suggesting that they may have signaling or transport, rather than structural, functions.…”
Section: Introductionmentioning
confidence: 99%